Perceived Research Publication Pressure on Academics: An Exploratory Study at The Open University of Sri Lanka - Radhika De Silva (The Open University of Sri Lanka, 2022)
Research is vital for development of any discipline. Academics in universities are also expected to engage in research in their discipline or other areas of interest and publish them in reputed journals. In most of the universities worldwide, the quantity of research publications has become the main criterion for recruitment, promotion, grants, and other incentives for academics. Many academics in Sri Lankan universities too experience pressure to publish and the pressure comes from different sources. Hence, the need to conduct research on publication experience of academics of The Open University of Sri Lanka (OUSL) was felt necessary. The objectives of this research were to identify the level of publication pressure experienced by a sample of academics at OUSL and to find out the factors that influence their research performance. This study used a survey research design. The revised Publication Pressure Questionnaire (PPQr) by Haven, Bouter, Smulders & Tijdink (2019) with an additional open-ended question was used as the data collection instrument. The findings showed that the academics in the sample experience research publication pressure to a considerable extent. The findings of this exploratory study will be used to adapt the questionnaire to suit the Sri Lankan University context, especially the Open and Distance teaching context.